Deteksi Dini Resiko Penyakit Jantung Pada Pasien Hipertensi - Sukarmin, Sukarmin; Islami; Khasanah, Iswatun (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Hypertension remains a prominent problem in Indonesian society that is almost equal in all regions with a fairly high incidence rate. According to the WHO, there are 1.28 billion hypertensive patients worldwide. In Indonesia, the prevalence of hypertension in 2018 was 34.1% or as many as 70 million people suffer from high blood pressure. The most common complications of hypertension are strokes and heart attacks. The purpose of this community service is to improve the ability of the detection to heart attack in people who experience hypertensiveness so that prevention can be carried out from the beginning. Early detection as an attempt to prevent hypertension from becoming a heart attack. The initial evaluation of five hypertensive patients, three of whom suffered from pain in the chest that sometimes disappeared, a sudden feeling of drowning and a feeling of frostbite. This dedication was conducted at the Village Clinic Kedungwinong Sukolilo Pati which involved 10 patients with hypertension. All these patients don't know how to detect early hypertension to avoid complications of heart disease.All five of them have not known and have never done a heart attack screening. The results of the screening training involving 10 hypertensive patients with the practice of giving a mark on the items early signs of a heart attack obtained 6 people had a good screening filling capacity, 2 people have a less filling screening capacity.